Dampak Implementasi Teknologi Mobile Terhadap Perubahan Perilaku Konsumen dalam Digital Marketing Media Shopee - Angga, Angga; Veri, Jhon (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The development of mobile technology has revolutionized the world of digital marketing, changing the interaction patterns between consumers and e-commerce platforms like Shopee. This research aims to evaluate the impact of mobile technology implementation on consumer behavior changes, especially in the context of digital marketing carried out through the Shopee medium. The approach used is a qualitative method with data collection through literature study. The data analysis technique used is content analysis. The research results indicate that mobile technology significantly influences consumer behavior in terms of time efficiency, transaction convenience, and increased loyalty to platforms. Features such as content personalization, promotional notifications, and ease of access are the main factors driving changes in consumer behavior. Additionally, this technology also assists business actors, particularly in enhancing the effectiveness of marketing campaigns and reducing distribution and intermediation costs. This study concludes that the utilization of mobile technology in digital marketing, if optimized correctly, can strengthen the relationship between consumers and business actors in the digital economy era.